Ratios of forbidden [OIII] λλ4959,5007 and [NII] λλ6548,6583 lines in nearby narrow emission line galaxies - Bon, Natas̆a; Bon, Edi; Marziani, Paola; Popović, Luka C̆. (Frontiers in Astronomy and Space Sciences, 2025)
Galaxies with narrow emission lines play a crucial role in testing the theoretical values of transition probabilities, especially for lines that need conditions that are hard to produce in laboratory plasma, and hence the theoretical values could not be checked in experimental measurements. In this paper, we explore the [O III]λλ4959,5007 and the [N II]λλ6,548, 6,583 doublets and their line ratios in a volume limited samples (0.01 ⩽ z ⩽ 0.05) of Sy2, LINERs, composite objects and star-forming galaxies, that zooms in the central region of these objects. Our results confirm that the theoretical line ratios R([OIII])=2.98 and R([NII])=3.05 as predicted by Storey and Zeippen (2000) are consistent with observations of HII regions, for both line ratios. This agreement occurs under conditions minimally affected by reddening, corresponding to total-to-selective extinction ratios (RV) between 3.1 and 4.1. In contrast, Seyfert 2, LINER, and composite galaxies confirm the same theoretical prediction of the [OIII] line ratios in the case of stronger reddening (2.1≤RV≤3.1), while [NII] ratios stays slightly lower than predicted by Storey and Zeippen (2000), aligning more closer to the values reported by Galavis et al. (1997), or indicating a presence of environmental conditions that affects these line ratios. This discrepancy in [NII] ratios suggests that, beyond reddening effects, the physical conditions in the [NII]-emitting regions of active galaxies differ from those in HII regions. Shocks, variations in electron density, ionization mechanisms, and gas or dust composition may contribute to these differences.